Penerapan Kerajinan Gelang Berbasis Empati di Panti Asuhan Yarhima 4 - Alifiona, Vivi Nurhidayatul; Rosanti, Erine Farah; Sulistyowati, Rici Maulidya; Putri, Izzah Kamelia; Nadhifa, Gusti Ayu Fillaily; Ubay, Muhammad; Puspito, Agung Nugroho (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
This social and educational activity aims to foster empathy among university students through the application of handicraft skills, specifically the making of beaded bracelets, at Yarhima 4 Orphanage. Through this activity, students not only teach the technique of making beaded bracelets but also build communication, compassion, and a sense of sharing with others. The program is designed to create an enjoyable and interactive atmosphere while providing added value in the form of skills that can be developed by the children at the orphanage as potential entrepreneurial assets. The results of the activity showed increased enthusiasm, creativity, and participation from the children in the learning process, as well as the formation of positive emotional bonds between the students and the orphanage residents. Furthermore, this social activity serves as a means of applying the values of Pancasila in daily life, particularly the second principle, A Just and Civilized Humanity. This value is reflected in the students’ attitudes of empathy, care, and loving treatment toward the children of Yarhima 4 Orphanage. Overall, the results show that the values of Pancasila can effectively foster empathy and compassion for others.